Epidemiology of paediatric presentations with musculoskeletal problems in primary care - Albert Tan; Victoria Y. Strauss; Joanne Protheroe; Kate M. Dunn (BMC Musculoskeletal Disorders, 2018)
Abstract Background Musculoskeletal disease is a common cause of morbidity, but there is a paucity of musculoskeletal research focusing on paediatric populations, particularly in primary care settings. In particular, there is limited information on population consultation frequency in paediatric populations, and frequency varies by age and sex. Few studies have examined paediatric musculoskeletal consultation frequency for different body regions. The objective was to determine the annual consultation prevalence of regional musculoskeletal problems in children in primary care. Methods Musculoskeletal codes within the Read morbidity Code system were identified and grouped into body regions. Consultations for children aged three to seventeen in 2006 containing these codes were extracted from recorded consultations at twelve general practices contributing to a general practice consultation database (CiPCA). Annual consultation prevalence per 10,000 registered persons for the year 2006 was determined, stratified by age and sex, for problems in individual body regions. Results Over 8 % (8.27%, 95% CI 7.86 to 8.68%) of the 16,862 children consulted with a musculoskeletal problem during 2006. Annual consultation prevalence for any musculoskeletal problem was significantly higher in males than females (male: female prevalence ratio 1.18, 95% CI 1.06 to 1.31). Annual consultation prevalence increased with age and the most common body regions consulted for were the foot, knee and back all of which had over 100 consultations (109, 104 and 101 respectively) per 10,000 persons per year. Conclusions This study provides new and detailed information on patterns of paediatric musculoskeletal consultations in primary care. Musculoskeletal problems in children are varied and form a significant part of the paediatric primary care workload. The findings of this study may be used as a resource for planning future studies.